Conspiracy theories as engines of connection for enriched public debates on emerging technologies - Gabriel Dorthe (Communications Earth & Environment)
Abstract Conspiracy theories on COVID-19 mRNA vaccines and solar geoengineering (chemtrails) tend to reinforce one another, thereby posing significant challenges to public policy and scientific norms and generating confusion by conflating disparate issues. This paper is based on ongoing ethnographic fieldwork conducted in the United States, Germany, Switzerland, and France since 2015 in these two areas of active conspiracy attention, involving observation of social media pages and blogs, active participation in gatherings, and semi-structured interviews. Here, I adopt a diplomatic perspective, highlighting the reciprocal suspicion between science policy and conspiratorial thinking in a competition between two sets of connections of scientific facts, values, politics, fears, and hopes. The present study suggests that the contamination of the scientific discourse by seemingly unrelated claims in conspiracy theories offers fruitful insights to science communication into how publics make sense of science and technology in the fierce debates surrounding immunization and climate policy.